Silencing of Plasma Membrane Ca(2+)-ATPase Isoforms 2 and 3 Impairs Energy Metabolism in Differentiating PC12 Cells - Boczek, Tomasz (Hindawi Publishing Corporation, 2014)
A close link between Ca(2+), ATP level, and neurogenesis is apparent; however, the molecular mechanisms of this relationship have not been completely elucidated. Transient elevations of cytosolic Ca(2+) may boost ATP synthesis, but ATP is also consumed by ion pumps to maintain a low Ca(2+) in cytosol. In differentiation process plasma membrane Ca(2+) ATPase (PMCA) is considered as one of the major players for Ca(2+) homeostasis. From four PMCA isoforms, the fastest PMCA2 and PMCA3 are expressed predominantly in excitable cells. In the present study we assessed whether PMCA isoform composition may affect energy balance in differentiating PC12 cells. We found that PMCA2-downregulated cells showed higher basal O(2) consumption, lower NAD(P)H level, and increased activity of ETC. These changes associated with higher [Ca(2+)](c) resulted in elevated ATP level. Since PMCA2-reduced cells demonstrated greatest sensitivity to ETC inhibition, we suppose that the main source of energy for PMCA isoforms 1, 3, and 4 was oxidative phosphorylation. Contrary, cells with unchanged PMCA2 expression exhibited prevalence of glycolysis in ATP generation. Our results with PMCA2- or PMCA3-downregulated lines provide an evidence of a novel role of PMCA isoforms in regulation of bioenergetic pathways, and mitochondrial activity and maintenance of ATP level during PC12 cells differentiation.